Second language speaking anxiety among undergraduates of Faculty of Education in UiTM Shah Alam / Noraisya Sofea Muhammad - Muhammad, Noraisya Sofea (2014)
Anxiety has been identified as one of the causes of problem in language learning. There are numerous studies regarding the students' speaking anxiety at the various levels. This research has given an insight about second language speaking anxiety among undergraduates of Faculty of Education in Universiti Teknologi Mara, Shah Alam by focusing on ESL speaking anxiety either in classroom or outside of the classroom. The purpose of this study is i) to investigate the level of anxiety among the students, ii) to compare the relationship between the level of anxiety and age of the students and iii) to identify the factors contribute to anxiety among 1st semester students and 8th semester students in second language speaking. The method used in this research is a survey. A questionnaire which is adapted from Foreign Language Classroom Anxiety Scale (FLCAS) by Horwitz, Horwitz & Cope is used to measure students' anxiety in speaking.